IMPLEMENTASI UNDANG-UNDANG NOMOR 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK DI KOMISI PEMILIHAN UMUM KABUPATEN SUMEDANG - Ade Opik Rohmanudin; Ai Endah Komalasari; Bayu Heryanto; Intan Fitri; Rani Raswati; Yuki Hildan Maulana (JRPA - Journal of Regional Public Administration, 2023)
The purpose of research research conducted is to inform the Implementation of Undang-Undang Number 14 of 2008 concerning the Disclosure of Punlik Information in the Sumedang District General Selection Commission. This Research Method uses qualitative methods. The sampling technique used is side purposive. with the information of Research: General functional technical organizers of elections, participation and humas, Chairman of the socialization division, education of voters, public participation, and human resources, Public functionalities of law and SDM, Technical case of the organizers of elections, participation and humas, Kasubag planning, data and info. As for technical data collections conducted, library studies and field studies consisting of observations, interviews, and documentation while data processing procedures in in inin research, namely data reduction, data display, withdrawal of verification conclusions, and triangulations. Market Research Results, can research research suggests that Implementation of Undang-Undang Number 14 Year 2008 About Public Information Disclosure in the Sumedang District General Selection Commission has been running at a maximum, shown from the Implementation of Public Information Disclosure of Public Information Discuss two ways that are directly and through the online media. The barriers in the Implementation of the Decree Policy No. 14 of 2008 About the Public Information Disclosure in the Sumedang District General Selection Commission has been quite top with the regulation of the Indonesian KPU, there is a lack of human resources in the General Selection Commission. As well as the Trust conducted the General Selection Commission against the Implementation of the Decree Policy No. 14 of 2008 concerning Public Information Disclosure in the Sumedang District General Selection Commission on the efforts of the lack of human resources by holding a picket schedule.